Acarofauna associated with coffee shrubs in relation to the distance of forest fragments - Carvalho, Thaiana Mansur Botelho; Reis, Paulo Rebelles; Silva, Ester Azevedo; Teodoro, Adenir Vieira (Coffee Science - ISSN 1984-3909, 2012)
The conversion of natural habitats into agriculture ones and the simplification of the structure of landscapes are the main causes of the global loss of biodiversity. Agroecosystems, especially monocultures, normally provide food resources and benefit organisms only when surrounded by forests. Mites (Arachnida: Acari) are one of the most diverse groups of arthropods and contribute to the function of ecosystems and agroecosystems. We aimed at determining the response of the coffee mite community to the distance from adjacent forest fragments. We evaluated leaves of coffee shrubs which were naturally found in the interior (0 m) and edge (25 m) of the fragments and in full sun coffee plantations located at 50 and 100 m in relation to the interior of the fragments. Although there was no pattern of reduction of mite abundance in relation to the distance from the centre of the forest fragments according with linear regressions, faunistic analyses revealed that abundance, dominance and frequency levels for some mite families were influenced by the distance from the centre of the forest fragments.